1980
DOI: 10.1161/01.cir.62.1.97
|View full text |Cite
|
Sign up to set email alerts
|

The association between urinary sodium excretion and blood pressure in children.

Abstract: SUMMARY This study explored the association between sodium excretion and blood pressure (BP). A new method was used to minimize the measurement error introduced by the large intrinsic variability of 24-hour sodium excretion. The ratio of intra-to interindividual variation was used to estimate the number of measurements needed to characterize the individual. When seven consecutive 24-hour samples were collected from 73 children, ages 11-14 years, a significant correlation between mean individual sodium excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
2

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 30 publications
3
40
0
2
Order By: Relevance
“…Our finding that salt intake is significantly related to blood pressure is in agreement with the study by Cooper et al 13 who measured sodium excretion from seven consecutive 24-h urine samples in 73 children aged 11-14 years. They found that an increase of 1 g/day in salt intake was associated with an increase of 1 mm Hg in systolic blood pressure, which is greater than that observed in our analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that salt intake is significantly related to blood pressure is in agreement with the study by Cooper et al 13 who measured sodium excretion from seven consecutive 24-h urine samples in 73 children aged 11-14 years. They found that an increase of 1 g/day in salt intake was associated with an increase of 1 mm Hg in systolic blood pressure, which is greater than that observed in our analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Measuring sodium from 24-h urine collections is the most accurate method in assessing dietary salt intake. In a carefully conducted study, where seven consecutive 24-h urines were collected by all participants, Cooper et al, 13 in 1980, demonstrated a significant linear relationship between urinary sodium and systolic blood pressure in 73 children aged 11-14 years, that is, the higher the salt intake, the higher the systolic blood pressure. The relationship remained significant after controlling for confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As in adults, the positive relationship between salt intake and blood pressure has already been reported in children. [14][15][16][17][18][19] A large cross-sectional study in Great Britain that investigated 1658 children and adolescents with a mean age of 11±0.1 years showed a significant association of salt intake with systolic blood pressure (SBP). 14 That study estimated that increasing salt intake by 1 g per day would relate to an SBP increase of 0.4 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the 1980 clinical study by Cooper on 73 black and white school children in Chicago detected what the authors described as a 'quantitatively weak' (although their findings of a 1 mm Hg per gram of sodium increase was greater than seen here) but significant (P ¼ 0.045) relation of sodium to blood pressure. 10 In Chicago, as opposed to the current study, urine collection replaced dietary recall as the basis of estimating sodium intake. Because the earlier study did not capture energy intake and could not assess its potentially confounding effect.…”
mentioning
confidence: 95%
“…Children who exercise vigorously may have large energy (and sodium) intakes, and be taller and leaner than youngsters who have the same body mass index and different life styles. Cooper et al 10 postulated that the strong link of creatinine to blood pressure might reflect muscle mass and perhaps be a marker of body size. This, in turn, might be the most powerful determinant of blood pressure in children-more important than age or sodium.…”
mentioning
confidence: 99%